Economic Value of Use of Organge as the Coagulant and Subtitution of Koro Tunggak in Making of Tofu - Wahyu Setyai Ratri (Agros Journal of Agriculture Science, 2017)
Oranges as one of the local fruit that many benefits it can serve as a coagulant in the making of tofu. The objectives of the research were: (1) to prove the effect of the use of oranges as coagulant and koro tunggak for soybean substitution in tofu production process, (2) to calculate production cost of tofu manufacture from organic frown. The study used organoleptic test. Obtained data that 90 percent of respondents can not distinguish between the texture, taste, color, and aroma between nutritious tofu and ordinary tofu. Protein content and antioxidants nutrientious tofu were higher than regular tofu. The fat content between nutritious tofu and ordinary tofu is the same. From an economic point of view, to produce nutritious tofu once more costs less than regular tofu, so the profit of producing nutritious tofu is higher than ordinary tofu. There is an opportunity to utilize oranges as a substitute for chemical ingredients because oranges can be obtained easily and the use of koro tunggak as a substitute of soybeans. Waste from the process of making tofu (whey tofu) can be processed into nata or kefir as the basic ingredients of cosmetics. Key-words: tofu, soybeans, koro tunggak